A Comparative Study of Paternity Leave Regulations in Indonesia and Australia: (A Labor Law Perspective) - Diana Setiawati; Mashari, Hanif Bagus; Apriansah, Rizki (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Paternity leave is a special entitlement granted to male employees to take time off from work to accompany their spouses during pregnancy, childbirth, and the early stages of childcare. The existence of paternity leave plays an important role in balancing opportunities between men and women, thereby fostering a gender-friendly workplace environment. In Indonesia, the right to paternity leave has been regulated under Law No. 13 of 2003 concerning Manpower and Law No. 4 of 2024 concerning Maternal and Child Welfare during the First 1,000 Days of Life. Meanwhile, in Australia, paternity leave is comprehensively regulated under the Fair Work Act 2009. This research aims to provide a comparative analysis of paternity leave regulations in Indonesia and Australia from a labor law perspective. The study adopts a normative juridical method with a comparative approach, relying on primary and secondary legal materials obtained through a literature study. The findings reveal that Indonesia provides only limited entitlements to paternity leave, both in terms of duration and implementation, with weak legal protection. In contrast, Australia offers a more developed framework under the Fair Work Act 2009, which includes longer leave duration, the possibility of extensions, and structured payment schemes. These provisions reflect Australia’s stronger commitment to gender equality, family welfare, and the recognition of fathers’ roles in child-rearing. The study concludes that Indonesia’s regulatory framework requires harmonization with international standards, particularly by adopting key aspects of the Australian model. Strengthening the legal protection of paternity leave in Indonesia is essential to promote gender equality in the workplace and within the family, while also supporting fathers’ active participation in childcare.